Mg2Sn-based thermoelectric material and preparation method and application thereof

Mg2Sn-based thermoelectric materials are directly synthesized in the air by Mg saturation temperature smelting method, solving the problems of high cost and complex processes in the prior art, and achieving efficient and simple preparation processes and obtaining high-performance materials.

CN119816181APending Publication Date: 2025-04-11INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015656.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has high cost and complex processes when preparing Mg2Sn thermoelectric materials. Due to the volatility and high reactivity of Mg elements, element ratio imbalance and impurities generation are caused, which affects the thermoelectric properties of the material.

Method used

Mg saturation temperature smelting method is used to directly and quickly synthesize Mg2Sn-based thermoelectric materials in the air. By controlling the critical point of saturation temperature of Mg, avoiding providing a vacuum or inert gas environment and using cover or solvent protection, simplifying the process flow.

Benefits of technology

The rapid synthesis of high-performance Mg2Sn-based thermoelectric materials in the air is achieved, which significantly shortens the production cycle, reduces process costs, and improves the thermoelectric properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816181A_ABST
    Figure CN119816181A_ABST
Patent Text Reader

Abstract

The invention discloses an Mg2Sn-based thermoelectric material and a preparation method and application thereof, and relates to the technical field of thermoelectric materials. According to the method, the Mg2Sn-based thermoelectric material is directly synthesized in one step by adopting an Mg saturation temperature smelting method, the Mg2Sn-based block material is rapidly smelted and synthesized in the air by controlling the Mg saturation temperature critical point without providing a vacuum or inert gas environment, a covering agent and solvent protection and secondary sintering, and the single-phase high-performance Mg2Sn-based thermoelectric material is obtained. The n-type and p-type materials under the same thermoelectric material system of Mg2Sn can be obtained by doping other elements through a Mg saturation temperature smelting method, the conductivity and the power factor of the Mg2Sn-based thermoelectric material are improved, the thermal conductivity of the Mg2Sn-based thermoelectric material is reduced, and the thermoelectric figure of merit is improved; the novel Mg saturation temperature smelting method can effectively reduce the production cost and improve the production efficiency, and is of great significance to the application of Mg2Sn-based thermoelectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to a Mg2Sn-based thermoelectric material and a preparation method and application thereof. Background Art

[0002] Thermoelectric materials are new energy materials that can directly realize the mutual conversion of heat energy and electric energy. Thermoelectric conversion technology is considered to be one of the technologies that is expected to solve the problem of large-scale low-grade waste heat. Thermoelectric power generation or refrigeration devices developed based on this technology have the advantages of simple structure, durability, no noise, no pollution, etc. The dimensionless thermoelectric figure of merit ZT value is usually used to measure the performance of thermoelectric materials.

[0003]

[0004] Among them, S is the Seebeck coefficient; σ is the electrical conductivity; κ is the total thermal conductivity; T is the absolute temperature.

[0005] As can be seen from the above formula, the thermoelectric performance of the material can be improved by increasing the Seebeck coefficient or electrical conductivity and reducing thermal conductivity, but the above parameters are not independent of each other, but are coupled to each other. Mg2Sn material has the characteristics and advantages of a large Seebeck coefficient, good chemical stability in the working temperature range, abundant reserves of elements in the earth's crust, environmental friendliness, and low density. It is a potential medium-temperature thermoelectric material with broad application prospects in the fields of temperature difference power generation and thermoelectric refrigeration.

[0006] In recent years, smelting and heat treatment are commonly used to prepare Mg-Sn alloys. However, during the smelting process, a covering agent, inert gas or other solvent is usually required to protect it. After smelting, the melt is injected into a preheated mold to obtain an alloy casting. However, the smelting method has the following defects: (1) Due to the extremely high vapor pressure and high chemical activity of Mg, Mg is easily volatilized during the high-temperature preparation process, resulting in an imbalance in the element ratio; (2) The melting point of Mg is 923K, while the melting point of Sn is 505.08K. Due to the large difference in their melting points, the sample grains are unevenly distributed and impurities and second phases appear; (3) Mg is easily reacted with O2 in the air to form MgO impurities. Due to its insulating properties, the material conductivity σ is greatly reduced. Excessive MgO impurity content will cause intergranular fragmentation of the material, reducing the success rate of preparing high-performance Mg2Sn materials and limiting the optimization of the material's thermoelectric properties.

[0007] Due to the above limitations, the prior art preparation process of Mg2Sn requires a vacuum or inert gas environment, a covering agent and a solvent to protect against magnesium burning, which increases the preparation cost and makes the preparation process relatively complicated. Therefore, how to improve the production efficiency of Mg2Sn thermoelectric materials while reducing the preparation cost is an urgent problem to be solved.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a Mg2Sn-based thermoelectric material and a preparation method and application thereof, aiming to improve the production efficiency of the Mg2Sn thermoelectric material while reducing the process cost.

[0010] The present invention is achieved in that:

[0011] In a first aspect, the present invention provides a method for preparing a Mg2Sn-based thermoelectric material, comprising: heating a magnesium source to a Mg saturation temperature, and then adding a tin source into a Mg melt for a direct mixing reaction.

[0012] In an optional embodiment, a high-frequency induction furnace is used to heat the magnesium source in an air atmosphere, and when the Mg saturation temperature point is reached and the Mg melt is not boiling, the tin source is added to the Mg melt for mixing.

[0013] In an optional embodiment, the high-frequency induction furnace is controlled to heat up to 1200K-1300K at a heating rate of 20K / s-30K / s.

[0014] In an optional embodiment, the magnesium source is heated to 1200K-1300K, mixed with the tin source, and the reaction container is shaken for 5s-10s.

[0015] In an optional embodiment, the molar ratio of magnesium in the magnesium source to tin in the tin source is (2.02-2.04):1.

[0016] In an optional embodiment, the reaction vessel is a graphite crucible;

[0017] Preferably, the diameter of the graphite crucible is 10 mm-100 mm.

[0018] In an optional embodiment, a doping source is added together with the tin source, and the doping element in the doping source is selected from at least one of Bi, Sb, Ag and Cu;

[0019] Preferably, the doping element in the doping source is Ag or Bi, and the chemical formula of the prepared Mg2Sn-based thermoelectric material is Mg 1.99 SnAg 0.01 or Mg2Sn 0.95 Bi 0.05 .

[0020] In an optional embodiment, after the reaction with the tin source is completed, the heating device is turned off, cooled to room temperature, and then demolded;

[0021] Preferably, the method further comprises: grinding and polishing the ingot obtained by demoulding.

[0022] In a second aspect, the present invention provides a Mg2Sn-based thermoelectric material prepared by any one of the preparation methods in the aforementioned embodiments;

[0023] Preferably, the electrical conductivity of the Mg2Sn-based thermoelectric material reaches 1×10 4 S / cm, and the absolute value of the Seebeck coefficient reaches 174μV / K;

[0024] Preferably, the Mg2Sn-based thermoelectric material is an n-type Mg2Sn-based thermoelectric material having a thermoelectric figure of merit greater than 1.

[0025] In a third aspect, the present invention provides an application of the Mg2Sn-based thermoelectric material of the aforementioned embodiment in temperature difference power generation or thermoelectric refrigeration.

[0026] The present invention has the following beneficial effects: the present invention adopts the Mg saturation temperature melting method to directly synthesize the Mg2Sn-based thermoelectric material in one step, and by controlling the critical point of the Mg saturation temperature, there is no need to provide a vacuum or inert gas environment, no need to provide a covering agent and solvent protection, and no need for secondary sintering, so as to achieve rapid melting and synthesis of the Mg2Sn-based bulk material in the air, and obtain a single-phase high-performance Mg2Sn-based thermoelectric material. The preparation method provided by the present invention is simple and easy, and can significantly shorten the production cycle. The entire production process only takes 3min-5min, which not only significantly reduces the process cost, but also has great significance for the application of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 is a SEM image of the Mg2Sn-based material prepared in an embodiment of the present invention;

[0029] Figure 2 is the XRD pattern of the Mg2Sn-based material prepared in the embodiment of the present invention;

[0030] Figure 3 is a conductivity diagram of the Mg2Sn-based material prepared in an embodiment of the present invention;

[0031] Figure 4 is a diagram of the Seebeck coefficient of the Mg2Sn-based material prepared in an embodiment of the present invention;

[0032] Figure 5 is a power factor diagram of the Mg2Sn-based material prepared in an embodiment of the present invention;

[0033] Figure 6 is a thermal conductivity diagram of the Mg2Sn-based material prepared in an embodiment of the present invention;

[0034] Figure 7 2 is a thermoelectric figure of merit of the Mg2Sn-based material prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0036] The embodiment of the present invention provides a method for preparing a Mg2Sn-based thermoelectric material, which uses a Mg saturation temperature smelting method to directly and quickly synthesize a Mg2Sn bulk material in air, and the steps are as follows:

[0037] S1. Prepare materials

[0038] Prepare a magnesium source and a tin source for the reaction. The magnesium source can be a commercially available metal Mg block, and the tin source can be a commercially available metal Sn particle.

[0039] In some embodiments, the molar ratio of magnesium in the magnesium source to tin in the tin source is (2.02-2.04):1. The molar ratio of the Mg element is 0.02mol%-0.04mol% in excess. The use of a slight excess of magnesium can effectively compensate for the trace volatilization and oxidation of the Mg element during the high-temperature smelting process, and the prepared Mg2Sn-based material does not contain impurities.

[0040] If doped materials need to be prepared, the required bulk materials can be weighed according to the molar ratio of the doping elements. By doping with other metal elements, n-type and p-type Mg2Sn-based semiconductor thermoelectric materials of the same system can be obtained.

[0041] Prepare a reaction container, such as a graphite crucible, but not limited thereto, and general high-temperature resistant containers are suitable for the preparation method provided in the embodiment of the present invention. The diameter of the graphite crucible is Φ10mm-Φ100mm, such as Φ10mm, Φ15mm, Φ20mm, Φ25mm, Φ30mm, Φ35mm, Φ40mm, Φ45mm, Φ50mm, Φ55mm, Φ60mm, Φ65mm, Φ70mm, Φ75mm, Φ80mm, Φ85mm, Φ90mm, Φ95mm, Φ100mm, etc.

[0042] S2. Melting reaction

[0043] Heat the magnesium source to the Mg saturation temperature (923K < Mg saturation temperature < 1364K), and then put the tin source into the molten Mg for direct mixing reaction. In the actual operation process, a high-frequency induction furnace can be used to heat the magnesium source in an air atmosphere. When the Mg saturation temperature point is reached and the molten Mg does not boil, put the tin source into the molten Mg for mixing. By controlling the critical point of the Mg saturation temperature, Mg2Sn materials can be rapidly smelted in air.

[0044] In some embodiments, the graphite crucible and the metal block do not need to be preheated in advance. Put the weighed metal Mg block directly into the graphite crucible, control the high-frequency induction furnace to heat up at a heating rate of 20K / s - 30K / s to 1200K - 1300K. When the Mg saturation temperature point is reached but the molten Mg does not boil, quickly put the Sn grains and the metal particles of the doped elements into the graphite crucible, and use the crucible tongs to shake the graphite crucible evenly 3 - 5 times until the reaction is complete (the reaction time is 5s - 10s), then turn off the induction heating device. The total reaction process takes 3min - 5min.

[0045] Specifically, the heating rate of the high-frequency induction furnace can be 20K / s, 23K / s, 25K / s, 28K / s, 30K / s, etc., and the temperature of the heated system can be 1200K, 1230K, 1250K, 1280K, 1300K, etc. The reaction time after adding the Sn grains can be 5s, 8s, 10s, etc.

[0046] In the embodiments of the present invention, through the Mg saturation temperature smelting method, other elements can be directly doped into the Mg2Sn-based thermoelectric material in air. The doped elements in the doping source are selected from at least one of Bi, Sb, Ag, and Cu, and the doped elements can be any one or several of the above. Pure Mg2Sn is an n-type semiconductor. By doping elements such as Bi, Sb, Ag, and Cu into the Mg2Sn matrix, n-type and p-type Mg2Sn-based materials of the same type will be obtained.

[0047] In the preferred embodiments, the doped element in the doping source is Ag or Bi, and the chemical formula of the prepared Mg2Sn-based thermoelectric material is Mg 1.99 SnAg 0.01 or Mg2Sn 0.95 Bi 0.05 , by controlling the doped elements and the doping amount, p-type Mg 1.99 SnAg 0.01 and n-type Mg2Sn 0.95 Bi 0.05 are prepared, and the thermoelectric figure of merit is greatly increased to 0.19 and 1.03 respectively.

[0048] S3, demolding, grinding and polishing

[0049] After the reaction with the tin source is completed, the heating device is turned off, cooled to room temperature, and then demolded to take out the finished product. The embodiment of the present invention can quickly and efficiently prepare Mg2Sn-based materials, and the Mg2Sn-based bulk material at this time is a round ingot with a diameter of 10mm-100mm.

[0050] In some embodiments, after demolding, the sample surface is ground and polished to obtain a Mg2Sn bulk material with a uniform and smooth surface.

[0051] The present invention also provides a Mg2Sn-based thermoelectric material, which is prepared by the preparation method provided by the present invention. The Mg2Sn-based thermoelectric material is pure phase and does not contain impurities such as MgO, and its power factor is higher than 4.83mW / m·K. 2 .

[0052] It should be added that the electrical conductivity of the Mg2Sn-based thermoelectric material prepared in the embodiment of the present invention reaches 1×10 4 S / cm, and the absolute value of the Seebeck coefficient reaches 174μV / K. The preparation method provided in the embodiment of the present invention can prepare n-type Mg2Sn-based thermoelectric materials with a thermoelectric figure of merit greater than 1 and p-type Mg2Sn-based thermoelectric materials with a thermoelectric figure of merit of 0.19. The application of the Mg2Sn-based thermoelectric material provided in the embodiment of the present invention in temperature difference power generation or thermoelectric refrigeration has good power generation or refrigeration performance.

[0053] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0054] Example 1

[0055] This embodiment provides a method for preparing a Mg2Sn-based thermoelectric material. In this embodiment, Mg2Sn is prepared in the following steps:

[0056] (1) Weigh the metal Mg block and Sn particles at a molar ratio of 2.02:1 (referring to the molar ratio of Mg to Sn, the same below).

[0057] (2) The graphite crucible and metal block do not need to be preheated in advance. Place the weighed metal Mg block directly into a Φ20mm graphite crucible, and use a high-frequency induction furnace to quickly heat it to 1250K at a heating rate of 25K / s; when the Mg saturation temperature is reached but the Mg melt has not yet boiled, add Sn particles into the graphite crucible, use a crucible tongs to evenly shake the graphite crucible 3-5 times until complete reaction (reaction time is 5s-10s), and turn off the induction heating device. The above process takes a total of 3min-5min.

[0058] (3) After the crucible mold is cooled to room temperature, it is demolded and the finished product is taken out. The Mg2Sn-based material is prepared quickly and efficiently. At this time, the Mg2Sn-based bulk material is a round ingot with a diameter of 20 mm. The surface is ground and polished to obtain a Mg2Sn bulk material with a uniform and smooth surface.

[0059] Figure 1 The results of the scanning electron microscope (SEM) test of the Mg2Sn bulk material prepared in this embodiment are shown. It can be seen that the Mg2Sn bulk material prepared in this embodiment has a uniform microstructure, and the grains are fine and evenly distributed. The micromorphology of the magnesium-tin compound shows obvious grain boundaries and no obvious defects inside the grains. In addition, the SEM image also shows that there are no obvious pores or cracks in the Mg2Sn material, confirming the overall density and good mechanical properties of the material. This uniform and dense microstructure is crucial to improving the thermoelectric and electrochemical properties of the material, and lays a solid foundation for further research and application.

[0060] Example 2

[0061] This embodiment provides a method for preparing a Mg2Sn-based thermoelectric material. In this embodiment, p-type Mg2Sn is prepared in the following steps:

[0062] (1) Weigh metal Mg blocks, Sn particles, and Ag particles in a molar ratio of 2.01:1:0.01.

[0063] (2) The graphite crucible and metal block do not need to be preheated in advance. Place the weighed metal Mg block directly into a Φ20mm graphite crucible, and use a high-frequency induction furnace to quickly heat it to 1250K at a heating rate of 25K / s; when the Mg saturation temperature is reached but the Mg melt has not yet boiled, add Sn particles and Ag particles into the graphite crucible, use a crucible tongs to evenly shake the graphite crucible 3-5 times until complete reaction (reaction time is 10s), and turn off the induction heating device. The above process takes a total of 3min-5min.

[0064] (3) After the crucible mold cools to room temperature, demold it and take out the finished product. The p-type Mg2Sn-based thermoelectric material is prepared quickly and efficiently. 1.99 SnAg 0.01 The ingot is a round ingot with a diameter of 20 mm. The surface is ground and polished to obtain a p-type Mg 1.99 SnAg 0.01 Bulk material.

[0065] Example 3

[0066] This embodiment provides a method for preparing a Mg2Sn-based thermoelectric material. In this embodiment, n-type Mg2Sn is prepared in the following steps:

[0067] (1) According to the molar ratio of Mg element with an excess of 0.02 mol%, metal Mg block, Sn particles and Bi particles were weighed according to the molar ratio of 2.02:0.95:0.05.

[0068] (2) The graphite crucible and metal block do not need to be preheated in advance. Place the weighed metal Mg block directly into a Φ20mm graphite crucible, and use a high-frequency induction furnace to quickly heat it to 1250K at a heating rate of 20K / s-30K / s; when the Mg saturation temperature is reached but the Mg melt is not boiling, put Sn particles and Bi particles into the graphite crucible, use a crucible tongs to shake the graphite crucible evenly 3-5 times until complete reaction (reaction time is 5-10s), and turn off the induction heating device. The above process takes a total of 3-5 minutes.

[0069] (3) After the crucible mold cools to room temperature, demold it and take out the finished product. High-performance n-type Mg2Sn-based thermoelectric materials are prepared quickly and efficiently. 0.95 Bi 0.05 The round ingot is 20 mm in diameter. The surface is ground and polished to obtain n-type Mg2Sn with uniform and smooth surface. 0.95 Bi 0.05 Bulk material.

[0070] Example 4

[0071] The only difference from Example 1 is that the temperature after heating in step (2) is 1100 K. Compared with the Mg2Sn ingot prepared in Example 1, the prepared Mg2Sn round ingot is not uniform because the temperature does not reach the Mg saturation temperature, and some void defects exist in the ingot.

[0072] Example 5

[0073] The only difference from Example 1 is that the temperature after heating in step (2) is 1400 K. Too high a temperature causes overburning of the Mg2Sn ingot.

[0074] Example 6

[0075] The only difference from Example 2 is that the metal Mg block, Sn particles, and Ag particles are weighed in a molar ratio of 1.99:1:0.03. 1.97 SnAg 0.03 Ingot and Mg in Example 2 1.99 SnAg 0.01 Compared with the ingot, it also has a higher Seebeck coefficient, which increases to 117μV / K at 473K, but the conductivity is slightly lower than that of Mg 1.99 SnAg 0.01Ingot, only reaches 1173S / cm, the lowest thermal conductivity is 6.03W / m·K, and the highest thermoelectric figure of merit is 0.136.

[0076] Example 7

[0077] The only difference from Example 2 is that the metal Mg block, Sn particles, and Ag particles are weighed in a molar ratio of 1.97:1:0.05. 1.95 SnAg 0.05 Ingot and Mg in Example 2 1.99 SnAg 0.01 Compared with the ingot, the electrical conductivity is significantly increased to 1720S / cm, but the Seebeck coefficient is reduced as a whole, reaching only 128μV / K at the highest, the thermal conductivity is as low as 5.77W / m·K, and the thermoelectric figure of merit is as high as 0.12.

[0078] Example 8

[0079] The only difference from Example 3 is that the metal Mg block, Sn particles, and Bi particles are weighed according to a molar ratio of 2.02:0.99:0.01. 0.99 Bi 0.01 The conductivity of the ingot can reach up to 2493S / cm, which is comparable to that of Mg2Sn in Example 3. 0.95 Bi 0.05 The ingot contrast is relatively low, and the absolute value of the Seebeck coefficient can reach up to 193μV / K, which is significantly higher than that of Mg2Sn 0.95 Bi 0.05 Ingot, the lowest thermal conductivity is 3.44W / m·K, and the highest thermoelectric figure of merit is 0.66.

[0080] Example 9

[0081] The only difference from Example 3 is that the metal Mg block, Sn particles, and Bi particles are weighed in a molar ratio of 2.02:0.97:0.03. 0.99 Bi 0.01 The conductivity of the ingot can reach 2928S / cm, which is comparable to that of Mg2Sn in Example 3. 0.95 Bi 0.05 The ingot contrast is relatively low, and the absolute value of the Seebeck coefficient can reach up to 174μV / K, which is higher than that of Mg2Sn 0.95 Bi 0.05 Ingot, the lowest thermal conductivity is 2.78W / m·K, and the highest thermoelectric figure of merit is 0.98.

[0082] Comparative Example 1

[0083] This comparative example provides an existing method for preparing Mg2Sn-based thermoelectric materials. The currently available preparation methods are as follows: solid phase reaction combined with hot pressing sintering, mechanical alloying combined with spark plasma discharge sintering, radio frequency induction melting, induction melting in a vacuum-sealed Ta tube, and Bridgman growth method and other synthesis methods to prepare Mg2Sn solid thermoelectric materials, but the above preparation processes all need to be carried out for a long time under vacuum or inert atmosphere. Compared with Example 1, the preparation method in Example 1 is simple and efficient, which solves the key problem of complex and high cost preparation of Mg2Sn.

[0084] Test Example 1

[0085] The samples in test examples 1-3 were subjected to XRD test, and the test results are as follows: Figure 2 As shown, compared with the standard diffraction peak card (PDF#01-074-7057), the obtained samples are pure phase Mg2Sn, all of which are the face-centered cubic anti-fluorite crystal structures expected by the experiment.

[0086] Figure 3 Mg2Sn, p-type Mg 1.99 SnAg 0.01 and n-type Mg2Sn 0.95 Bi 0.05 The conductivity comparison of the samples at 323K-723K shows that the conductivity of Mg2Sn is as high as 1×10 4 S / cm, p-type Mg prepared in Example 2-3 1.99 SnAg 0.01 and n-type Mg2Sn 0.95 Bi 0.05 The electrical conductivities are as high as 1343S / cm and 4113S / cm respectively.

[0087] Figure 4 This is a comparison chart of the Seebeck coefficients of the samples of Examples 1-3 at 323K-723K. It can be seen that the absolute values ​​of the Seebeck coefficients of the p-type and n-type Mg2Sn thermoelectric materials successfully prepared in Examples 2-3 are increased to 162μV / K and 156μV / K.

[0088] Figure 5 The power factor comparison chart of the samples in Examples 1-3 at 323K-723K shows that the p-type and n-type Mg2Sn-based thermoelectric materials prepared in Examples 2-3 have a higher power factor of 1.79mW / m·K. 2 and 4.67mW / m·K 2 .

[0089] Figure 6It is a comparison chart of the thermal conductivities of the samples of Examples 1-3 at 323K-723K. The thermal conductivities of the p-type and n-type Mg2Sn thermoelectric materials prepared in Examples 2-3 are reduced to 4.47 W / m·K and 2.34 W / m·K.

[0090] Figure 7 It is a comparison chart of the thermoelectric figures of merit of samples in Examples 1-3 at 323K-723K. The thermoelectric figures of merit of p-type and n-type Mg2Sn-based thermoelectric materials prepared in Examples 2-3 are greatly improved to 0.19 and 1.03, respectively. The improvement of n-type Mg2Sn-based thermoelectric material is greater, and it has very good application prospects.

[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a Mg2Sn-based thermoelectric material, characterized in that: include: The magnesium source is heated to the Mg saturation temperature, and then the tin source is added to the Mg melt for direct mixing reaction.

2. The preparation method according to claim 1, characterized in that: The magnesium source is heated in an air atmosphere by using a high frequency induction furnace, and when the Mg saturation temperature point is reached and the Mg melt is not boiling, the tin source is added into the Mg melt for mixing.

3. The preparation method according to claim 2, characterized in that: The high-frequency induction furnace is controlled to heat up to 1200K-1300K at a heating rate of 20K / s-30K / s.

4. The preparation method according to claim 2, characterized in that: The magnesium source is heated to 1200K-1300K, mixed with the tin source, and the reaction container is shaken for 5s-10s.

5. The preparation method according to claim 4, characterized in that: The molar ratio of magnesium in the magnesium source to tin in the tin source is (2.02-2.04):

1.

6. The preparation method according to claim 4, characterized in that: The reaction container is a graphite crucible; Preferably, the diameter of the graphite crucible is 10 mm-100 mm.

7. The preparation method according to claim 1, characterized in that: When adding the tin source, a doping source is added together, wherein the doping element in the doping source is selected from at least one of Bi, Sb, Ag and Cu; Preferably, the doping element in the doping source is Ag or Bi, and the chemical formula of the prepared Mg2Sn-based thermoelectric material is Mg 1.99 SnAg 0.01 or Mg2Sn 0.95 Bi 0.05 .

8. The preparation method according to any one of claims 1 to 7, characterized in that: After the reaction with the tin source is completed, the heating device is turned off, the mixture is cooled to room temperature, and then demolded; Preferably, the method further comprises: grinding and polishing the ingot obtained by demoulding.

9. A Mg2Sn-based thermoelectric material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8; Preferably, the electrical conductivity of the Mg2Sn-based thermoelectric material reaches 1×10 4 S / cm, and the absolute value of the Seebeck coefficient reaches 174μV / K; Preferably, the Mg2Sn-based thermoelectric material is an n-type Mg2Sn-based thermoelectric material having a thermoelectric figure of merit greater than 1.

10. Use of the Mg2Sn-based thermoelectric material according to claim 9 in temperature difference power generation or thermoelectric refrigeration.